2022
DOI: 10.18488/61.v10i1.2842
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Formative Assessment Practices on Student Motivation for Learning the English Language

Abstract: This study aimed at exploring the impact of formative assessment practices on student motivation for learning the English language. As Leahy, Lyon, Thompson, and Wiliam (2005) stated, education needs to change its function from collecting the results of right or wrong, and to encourage teachers in gathering information that will affect the educational decisions. This study is a non-experimental, correlational study, to describe the relationship between formative assessment practices and motivation for leaning.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Student competency can be assessed in a comprehensive and sustainable manner. This finding is consistent with that of Muho and Taraj (2022) who also found formative outcomes include cognitive aspects (products and processes), affective, and psychomotor aspects obtained from the authentic assessment. The results indicated that students meet the standards of competence specified achievement.…”
Section: Discussionsupporting
confidence: 91%
“…Student competency can be assessed in a comprehensive and sustainable manner. This finding is consistent with that of Muho and Taraj (2022) who also found formative outcomes include cognitive aspects (products and processes), affective, and psychomotor aspects obtained from the authentic assessment. The results indicated that students meet the standards of competence specified achievement.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results are reported by Das et al and others that FA makes students self-directed and indepth learners. 9,16,17 In agreement with previous studies, the current study reported that FA also helps faculty and students to recognize the areas of strength and weakness in students without incurring any academic penalty. It also permits quick corrective action by them.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 19 existing studies on formative assessment practices, 6 examined formative assessment practices comprehensively [ 4 , [37] , [38] , [39] , [40] , [41] ]. The results suggest that formative assessment practices can aid in fostering students’ self-regulation by encouraging them to set goals, generating and responding to feedback and managing resources [ 40 ] thereby positively affecting student motivation and subsequent achievement [ 4 ].…”
Section: Resultsmentioning
confidence: 99%